2014
DOI: 10.1093/carcin/bgu033
|View full text |Cite
|
Sign up to set email alerts
|

Functional links between Snail-1 and Cx43 account for the recruitment of Cx43-positive cells into the invasive front of prostate cancer

Abstract: Suppressive function of connexin(Cx)43 in carcinogenesis was recently contested by reports that showed a multifaceted function of Cx43 in cancer progression. These studies did not attempt to model the dynamics of intratumoral heterogeneity involved in the metastatic cascade. An unorthodox look at the phenotypic heterogeneity of prostate cancer cells in vitro enabled us to identify links between Cx43 functions and Snail-1-regulated functional speciation of invasive cells. Incomplete Snail-1-dependent phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 57 publications
4
41
1
Order By: Relevance
“…Where indicated, cancer cells were stained with CellTracker Orange CMRA (10 µM, Invitrogen). For gap junctional intercellular coupling (GJIC) analyses, calcein-loaded (Invitrogen) donor (DU-145) cells were plated on monolayers of acceptor (HUVEC) cells grown on coverslips in Petri dishes at the ratio of 1:50 [39] to evaluate intercellular calcein transfer and coupling index defined as the percentage of donor cells coupled with at least one acceptor cell. To determine the cytotoxic effect of FF, HUVECs incubated with various concentrations of FF for 6, 24 and 48 h were harvested, and the number of viable cells was determined by the fluorescence diacetate/ethidium bromide test.…”
Section: Immunocytochemistry and Fluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Where indicated, cancer cells were stained with CellTracker Orange CMRA (10 µM, Invitrogen). For gap junctional intercellular coupling (GJIC) analyses, calcein-loaded (Invitrogen) donor (DU-145) cells were plated on monolayers of acceptor (HUVEC) cells grown on coverslips in Petri dishes at the ratio of 1:50 [39] to evaluate intercellular calcein transfer and coupling index defined as the percentage of donor cells coupled with at least one acceptor cell. To determine the cytotoxic effect of FF, HUVECs incubated with various concentrations of FF for 6, 24 and 48 h were harvested, and the number of viable cells was determined by the fluorescence diacetate/ethidium bromide test.…”
Section: Immunocytochemistry and Fluorescence Microscopymentioning
confidence: 99%
“…Image acquisition was performed with a Leica DMI6000B microscope (DMI7000 version; Leica Microsystems, Wetzlar, Germany) equipped with the Total Internal Reflection Fluorescence, Nomarski Differential Interference Contrast (DIC) and Interference Modulation Contrast (IMC) modules. LAS-AF deconvolution software was used for image processing as described previously [39]. Three dimensional (3D) images were registered using a Leica TCS SP5 confocal microscope (Leica Microsystems, Mannheim, Germany) using 63Â HCX PL APO CS oil immersion (NA 1.4) objective lens.…”
Section: Immunocytochemistry and Fluorescence Microscopymentioning
confidence: 99%
“…One can expect that, in heterogeneous cell populations such as populations of cancer cell lines (32,33), the cells that proliferate are present alongside cells that die by apoptosis or necrosis. The present study demonstrated that the inhibition of increased cell numbers in cancer cell cultures in the presence of 5-FU and 9-AAA resulted from an increased proportion of dying to proliferating cells over time.…”
Section: Discussionmentioning
confidence: 99%
“…1E and F; AT-2 P=0.016, P=0.01, P=0.01, P=0.01; MAT-LyLu P=0.018, P=0.01, P=0.01, P=0.01, respectively). At ii) In parallel, the samples from the same cell culture were analyzed with the modern method using FlowSight, which analyzes thousands of cells (33). The results obtained using the two methods combined yielded well-corresponding results (Fig.…”
Section: Cell Type-specific Effects Of 5-fu and 9-aaa Upon Growth Of mentioning
confidence: 90%
See 1 more Smart Citation